2000
DOI: 10.1002/1097-0290(20001120)70:4<436::aid-bit9>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of 16S-rRNA to investigate microbial population dynamics during biodegradation of toluene and phenol by a binary culture

Abstract: Interspecies interactions and changes in the rate and extent of biodegradation in mixed culture–mixed substrate studies were investigated. A binary mixed culture of Pseudomonas putida F1 and Burkholderia sp. JS150 degraded toluene, phenol, and their mixture. Both toluene and phenol can serve as sole sources of carbon and energy for both P. putida F1 and strain JS150. To investigate the population dynamics of this system, a fluorescent in‐situ hybridization method was chosen because of its ability to produce qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The investigation and characterization of mixed cultures is of increasing importance for basic research as well as for ecological, medical and biotechnological applications. These include, for example investigations of interactions of microbial populations (Fredrickson, 1982), differences between specialists and generalists in microbial interactions (Kuenen, 1982), metabolic interactions in mixed culture biofilms (Møller et al, 1998), susceptibility of mixed biofilms to disinfection (Whiteley et al, 2001), quorum sensing in mixed biofilms related to cystic fibrosis (Riedel et al, 2001), fingerprinting of estrogen degrading consortia (Yu et al, 2005), population dynamics in rice field soils (Lueders and Friedrich, 2000), Nisin production by a mixed culture (Shimizu et al, 1999), biodegradation by a binary culture (Rogers et al, 2000), degradation of phenols, benzoates, and phtalates by anaerobic mixed cultures (Levén and Schnürer, 2005). In addition, there are numerous theoretical considerations available on the dynamics of mixed cultures based on mathematical models for up to an infinite number of species available (e.g., Armstrong and McGehee, 1978;Hansen and Hubbell, 1980;Huisman and Weissing, 2001;Lobry and Harmand, 2005;Pilyugin et al, 2004;Smith and Waltman, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigation and characterization of mixed cultures is of increasing importance for basic research as well as for ecological, medical and biotechnological applications. These include, for example investigations of interactions of microbial populations (Fredrickson, 1982), differences between specialists and generalists in microbial interactions (Kuenen, 1982), metabolic interactions in mixed culture biofilms (Møller et al, 1998), susceptibility of mixed biofilms to disinfection (Whiteley et al, 2001), quorum sensing in mixed biofilms related to cystic fibrosis (Riedel et al, 2001), fingerprinting of estrogen degrading consortia (Yu et al, 2005), population dynamics in rice field soils (Lueders and Friedrich, 2000), Nisin production by a mixed culture (Shimizu et al, 1999), biodegradation by a binary culture (Rogers et al, 2000), degradation of phenols, benzoates, and phtalates by anaerobic mixed cultures (Levén and Schnürer, 2005). In addition, there are numerous theoretical considerations available on the dynamics of mixed cultures based on mathematical models for up to an infinite number of species available (e.g., Armstrong and McGehee, 1978;Hansen and Hubbell, 1980;Huisman and Weissing, 2001;Lobry and Harmand, 2005;Pilyugin et al, 2004;Smith and Waltman, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…For understanding underlying mechanisms of community dynamics in ecological, medical as well as in biotechnological applications the quantitative analysis of systems with reduced species number and its specific population dynamics is of great interest. Especially as kinetics derived from pure culture investigations in many cases are not sufficient for mathematical modeling of mixed culture kinetics and dynamics (Rogers et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…used to investigate the interactions of a co-culture of Pseudomonas putida F1 and Burkholderia sp. JS150 degrading toluene, phenol, and their mixture (Rogers et al, 2000). Based on their experience with the methods, the authors suggested that the results from this study encourage further investigations wherein substrates and microbial population are monitored simultaneously.…”
Section: Remediation Of Non-petroleum Compounds Fish With 16s Rrna-tmentioning
confidence: 81%
“…[5][6][7][8][9] Downloaded by [University of Hawaii at Manoa] at 15: 24 27 December 2014 In this study, it is therefore aimed to determine the effect of toluene on an anaerobic sludge taken from a fullscale upflow anaerobic sludge blanket (UASB) reactor in terms of potential activity and composition of acetoclastic methanogens. The SMA tests had been carried out to determine the effect of different toluene concentrations on the potential acetoclastic methanogenic activity of the anaerobic sludge.…”
Section: Introductionmentioning
confidence: 99%